Borax is Still Detected in Crackers Sold at Jenangan District Market Using the Rapid Test Method - Zilca, Ervalia Zamilanti; Narwati, Narwati; Marlik, Marlik; Rusmiati, Rusmiati; Nurmayanti, Demes (FORIKES, 2026)
Borax is a prohibited food additive according to the Regulation of the Minister of Health of the Republic of Indonesia Number 033 of 2012 because of its harmful effects on human health, including disorders of the central nervous system, kidney and liver dysfunction, and even death. Nevertheless, the use of borax is still suspected in certain food processing practices, including the production of crackers. This study aimed to determine the presence of borax in crackers sold at the market. This research used a descriptive design with organoleptic testing and qualitative borax testing using the rapid test method. The research objects were cracker products sold by three vendors in the Jenangan District Market. Total sampling was applied based on the total number of crackers sold by the vendors, resulting in 21 samples. The results of the organoleptic test showed that three samples had slightly dull colors and seven samples had textures that were difficult to crush. The qualitative rapid test results indicated that 14.3% of the cracker samples were positive for borax. Crackers containing borax were generally characterized by a dull appearance and a hard texture that was difficult to crush. In conclusion, borax was still found in a proportion of cracker products sold in the Jenangan District Market, indicating that the use of this prohibited additive persists in some food products and may pose potential health risks to consumers.Keywords: borax, crackers, organoleptic test, qualitative test